SHAREHOLDER VALUE CREATION THROUGH UNIQUE INTANGIBLES BY INDIAN CORPORATE’S- A CONCEPTUAL ANALYSIS - Singh, Pradeep Kumar (Journal of Contemporary Research in Management (JCRM), 2015)
Key Words: Value Creation, Market Capitalization, Intangible Assets, Amortization, Discloser & Reporting, ABSTRACT Value based management is one of the important aspect of modern management, especially for shareholders value creation. At present shareholders are not only interested in dividend paid by the company, they are equally interested in total value creation by the firm. In a long run value creation depends upon intangibles, because intangibles are closely related to value creation process of the corporate. The fundamental difference between the 20th century economy and current economy is shifting of focus from industrial base activities to service & knowledge base activities. In current knowledge economy, brands, patents, franchises, software’s, research programmes, ideas, human resources, their knowledge, expertise & skills, experience, methods and process, service networks, internal structure are the assets (Intangible) creates value for the business, which are having unique nature among the different industries. The main purpose of identification of unique intangible assets is to highlights the key intangibles in which corporate’s are investing huge amount and which are also responsible for their productivity and enhancement of value creation. Keeping this view researcher is trying to identify some unique intangibles (which are not common in other industries) according to specific nature of industry. A comprehensive survey made by the researcher among the top 60 BSE companies to know the method of recognitions of intangible assets, amortization/depreciation during the last one decade. This research article highlights identification of unique intangibles, role in value creation, amortization practices adopted by different industries for intangible assets.